Long-term effects of an early-life exposure of fathead minnows to sediments containing bitumen. Part I: Survival, deformities, and growth. (August 2019) - Vignet, C.; Frank, R.A.; Yang, C.; Wang, Z.; Shires, K.; Bree, M.; Sullivan, C.; Norwood, W.P.; Hewitt, L.M.; McMaster, M.E.; Parrott, J.L.
Abstract: The aim of this study was to investigate the long-term effects of a short exposure to natural sediments within the Athabasca oil sand formation to critical stages of embryo-larval development in fathead minnows ( Pimephales promelas ). Three different sediments were used: Ref sediment from the upper Steepbank River tested at 3 g/L (containing 12.2 ng/g ∑PAHs), and two bitumen-rich sediments tested at 1 and 3 g/L; one from the Ells River (Ells downstream, 6480 ng/g ∑PAHs) and one from the Steepbank River (Stp downstream, 4660 ng/g ∑PAHs). Eggs and larvae were exposed to sediments for 21 days, then transferred to clean water for a 5-month grow-out and recovery period. Larval fish had significantly decreased survival after exposure to 3 g/L sediment from Stp downstream, and decreased growth (length and weight at 16 days post hatch) in Ells and Stp downstream sediments at both 1 and 3 g/L. Decreased tail length was a sensitive endpoint in larval fish exposed to Ells and Stp downstream sediments for 21 days compared to Ref sediment. After the grow-out in clean water, all growth effects from the bitumen-containing sediments recovered, but adult fish from Stp downstream 3 g/L sediment had significant increases in jaw deformities. The study shows the potential for fish to recover from the decreased growth effects caused by sediments containing oil sands-related compounds, but that some effects of the early-life sediment exposure occur later on in adult fish. Graphical abstract: Image 1 Highlights: Early-life exposure of fish to bitumen-containing sediments from oil sands rivers. Larval fish had decreased growth and increased deformities after sediment exposure. Growth recovered after transfer to clean water for grow-out to maturity. Increased jaw deformities in adult fish. Abstract : Short early-life exposure to sediments containing bitumen leads to long-term effects in fathead minnow.